1990
DOI: 10.1080/00222895.1990.10735521
|View full text |Cite
|
Sign up to set email alerts
|

Perceptuomotor Compatibility in Pursuit Tracking of Two-Dimensional Movements

Abstract: ABSTRACT. In a previous article, we reported an investigation of visuomanual pursuit tracking of unpredictable two-dimensional targets. This article extends the study to the tracking of predictable stimuli. In both investigations, the target trajec tory was elliptical. The experimental factors we vari ed were the orientation of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 29 publications
(30 reference statements)
5
45
2
Order By: Relevance
“…In contrast to previous studies (Viviani 2002;Viviani and Mounoud 1990;Viviani et al 1987) but similar to findings of Wann et al (1988), the typical curvature-velocity relation as predicted by the 2/3 power law seems to be altered after motor training.…”
Section: Introductioncontrasting
confidence: 56%
“…In contrast to previous studies (Viviani 2002;Viviani and Mounoud 1990;Viviani et al 1987) but similar to findings of Wann et al (1988), the typical curvature-velocity relation as predicted by the 2/3 power law seems to be altered after motor training.…”
Section: Introductioncontrasting
confidence: 56%
“…Viviani and Stucchi (1992a) conducted experiments on the perception of curvilinear movement trajectories of a single point light. They found that trajectories obeying the kinematics of biological motion (expressed by an equation in which speed varies with the degree of curvature) were perceived as having uniform speed, even though the variations in speed in fact exceeded 200% (see also Viviani, Baud-Bovy, & Redolfi, 1997;Viviani & Mounoud, 1990;Viviani & Stucchi, 1989). These findings suggest that curvilinear movements are perceived, not in terms of actual changes in velocity, but in terms of wholistic gestures, which appear smooth and uniform when executed as a biological system would articulate them.…”
Section: Interpreting Point-light Displays and Apparent Motion Displaysmentioning
confidence: 99%
“…It has been suggested (Hoffman & Flinchbaugh, 1982) that these motor schemes are instrumental for providing a veridical three-dimensional (3D) interpretation of the retinal images. Moreover, further evidence of a motor component in the interpretation of visual information has come from the results of two experiments on visuomanual pursuit tracking (Viviani, Campadelli, & Mounoud, 1987;Viviani & Mounoud, 1990), which show that it is virtually impossible to accurately pursue two-dimensional (2D) targets that do not comply with certain regularities that characterize biological motions.…”
mentioning
confidence: 99%